Psychological distress is affected by fear of COVID-19 via lifestyle disruption and leisure restriction among older adults in Japan: a cross-sectional study - Zenba, Yosuke; Kobayashi, Akihiro; Imai, Tadanori (Frontiers in Public Health, 2023)
Introduction: Engaging in social activities is an essential component of a healthy lifestyle for community-dwelling older adults. Critically, as with past disasters, there is concern about the effects of long-term activity restrictions due to the coronavirus disease 2019 (COVID-19) pandemic on health of older adults. However, the precise associations between fear of COVID-19, lifestyle satisfaction, leisure activities, and psychological distress are unclear. Objective: The purpose of this study was to comprehensively determine the associations between fear of COVID-19, lifestyle satisfaction, leisure engagement, and psychological distress among community-dwelling older adults in the context of the ongoing COVID-19 pandemic. Material and methods: A questionnaire survey administered by mail was conducted from October 1 to October 15, 2021. The questionnaire included the Fear of COVID-19 Scale, the Lifestyle Satisfaction Scale, the Leisure Activity Scale for Contemporary Older Adults, and the Kessler Psychological Distress Scale-6. Based on previous studies, we developed a hypothetical model for the association between fear of COVID-19, lifestyle satisfaction, leisure engagement, and psychological distress and performed structural equation modeling to assess the relationships between these variables. Results: Participants included 301 Japanese citizens (23.6% male, 76.4% female), with a mean age of 76.7 ± 4.58 years. Goodness-of-fit from structural equation modeling was generally good. Analysis of standardized coefficients revealed a significant positive relationship between fear of COVID-19 and psychological distress (β = 0.33, p < 0.001) and lifestyle satisfaction and leisure activities (β = 0.35, p < 0.001). We further observed a significant negative relationship between fear of COVID-19 and lifestyle satisfaction (β = ‒0.23, p < 0.001) and between leisure activities and psychological distress (β = ‒0.33, p<0.001). Conclusion: Fear of COVID-19 is significantly associated with psychological distress, both directly and via its effects on lifestyle satisfaction and leisure activities. That is, not only did fear of COVID-19 directly impact psychological distress of participants, it also affected psychological distress through lifestyle disruption and leisure restriction. This results may be used to better understand how a national emergency that substantially restricts daily life, such as COVID-19 or an earthquake disaster, can affect the psychological health and well-being of older, community-dwelling adults.